Solution of Fractional Telegraph Equations by Conformable Double Convolution Laplace Transform - Osman, Waleed M.; Elzaki, Tarig M.; Siddig, Nagat A. A. (Communications in Mathematics and Applications, 2021)
This paper covers both conformable double Laplace transform and conformable double convolution, including their definitions, theorems and properties. The purpose of this research is to solve a fresh case of fractional telegraph equations with conformable double convolution by conformable double Laplace transform.
Keywords: Conformable double Laplace transform; Fractional telegraph equation; Conformable double convolution